TV digital: roteiro e protótipo de telejornal interativo baseado no conceito de infotretenimento - Vieira, Eloiza Cristina Fontes [UNESP] (2013)
The present work is based on an exploratory study on the relationships between the concepts of TV Journalism in the Digital TV in the Infotainment genre, which is defined as the program model that adopts the formula of a hybrid production following a line that lies or combines elements between information and entertainment. Therefore, a script model was developed. This technical reports presents the full script of the newscast that transmits information through entertainmet (Infotainment) as well as images of how the interactivity of this prototype works